The effects of canagliflozin, a sodium glucose co-transporter 2 inhibitor, on mineral metabolism and bone in patients with type 2 diabetes mellitus. (2nd August 2016) - Alba, Maria; Xie, John; Fung, Albert; Desai, Mehul
Abstract: Background: Sodium glucose co-transporter 2 (SGLT2) inhibitors lower blood glucose levels in patients with type 2 diabetes mellitus (T2DM) by increasing urinary glucose excretion. This review provides a comprehensive summary of preclinical and clinical data on the effects of the SGLT2 inhibitor canagliflozin on mineral balance and bone. Methods: Published articles and internal study reports through November 2015 were included. Results: In clinical studies, canagliflozin was not associated with meaningful changes in serum or urine calcium, parathyroid hormone, or vitamin D. Canagliflozin was associated with increases in serum magnesium and phosphate without changes in their urinary excretion. Increases in serum collagen type-1 beta-carboxy-telopeptide (beta-CTX), a bone resorption marker, and osteocalcin, a bone formation marker, were observed with canagliflozin. Decreases in total hip bone mineral density (BMD) of up to 1.2% were seen with canagliflozin after 2 years; no changes in BMD were seen at other skeletal sites. Changes in total hip BMD and serum beta-CTX with canagliflozin correlated with decreases in body weight. In a clinical program-wide analysis, canagliflozin was associated with increased fracture risk that was driven by a higher incidence in the cardiovascular safety study (CANVAS), with no fracture imbalance seen in pooled data from other Phase 3 studies. The fracture imbalance occurred within 12 weeks after initiating treatment, most frequently in the distal portion of the upper and lower extremities. Conclusions: Across clinical studies, canagliflozin did not meaningfully affect calcium homeostasis or hormones regulating calcium homeostasis. Increases in bone turnover markers and decreases in BMD at the total hip, but not at other sites, that correlated with weight loss were seen with canagliflozin. Canagliflozin was associated with a higher fracture incidence within 12 weeks, primarily in distal extremities. Data from ongoing canagliflozin studies will provide additional information on fracture risk.